Dietary iron overload. the generation of reactive oxygen species and hepatocarcinogenesis in experimental rats (Part 1) - Asare, G. A. (My University, 2003)
Dietary iron (Fe) overload, originally referred to as Bantu Visceral Siderosis, is an Reloading condition that is still prevalent in rural populations of sub-Saharan Africa. The better known Fe loading disease, hereditary haemochromatosis (HFI) is frequently complicated by hepatocellular carcinoma (HCC) and, in rare instances this occurs in the absence of cirrhosis. The latter, together with recent evidence that dietary Fe overload in the Black African carries an increased risk for HCC, suggests that excessive hepatic iron may itself be carcinogenic. The aim of the study was to determine if Fe alone could induce HCC in experimental rat models and, if so, to investigate possible mechanisms of hepatocarcinogenesis. 360 Wistar albino rats (Rattus norvegicus) were divided into 6 groups. The first group, the control animals, was designated C group. Groups 2-6 were Fe-fed alone or in combination with other chemicals: group 2 Fe alone (Fe group), group 3 (Fe + V) vitamins A & E supplementation [50 mg all trans-retinol (vitamin A) and 500 mg a-tocopherol (vitamin E) per kg diet], group 4 (Fe - V) received a diet totally devoid of vitamins A & E, group 5 (Fe + ASA) received 20 mg aspirin (ASA) per day, group 6 (Fe + Cu) received 300 mg/kg diet of copper sulphate (CuS04) supplementation for 12 months followed by 3% copper hydroxide carbonate [CuC03»Cu(0H)2]
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand In fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2003
Keywords: hepatocarcinogenesis; Overload, Iron; Iron, Dietary; Laboratory Rats; Reactive Oxygen Species